2008
DOI: 10.1007/s11738-008-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious bud regeneration from leaf explants of Platanus occidentalis L. and genetic stability assessment

Abstract: The aim of this work is to develop a method of plant regeneration from leaf explants of Platanus occidentalis L. successfully. Woody plant medium (HortScience 16:453-459, 1981) and Murashige and Skoog (Physiol Plant 15:473-497, 1962) medium were used as induced and rooted basal medium, respectively. The effects of combinations of 6-BA, IBA, NAA and KT with different concentrations on adventitious bud regeneration from P. occidentalis leaf explants were compared. The results showed that the highest shoot reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The most important factor influencing bud differentiation is the type of growth regulator used especially the type of cytokinin [2,13]. Its concentration in the culture medium is critical for shoot organogenesis [14]. The promoter effect of BAP in the induction of multiple shoots has previously been reported [15].…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor influencing bud differentiation is the type of growth regulator used especially the type of cytokinin [2,13]. Its concentration in the culture medium is critical for shoot organogenesis [14]. The promoter effect of BAP in the induction of multiple shoots has previously been reported [15].…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration via adventitious shoots in woody species has been reported in Dalbergia latifolia (Lakshmisita et al 1986), Aegle marmelos (Islam et al 1993), Sesbania grandiflora (Detrez et al 1994), Liquidambar styraciflua (Kim et al 1997), Prunus avium (Hammatt and Grant 1998), D. sissoo (Pradhan et al 1998;Chand et al 2002), Azadirachta indica (Eswara et al 1998;Sharma et al 2002), Salix nigra (Lyyra et al 2006), Paulownia tomentosa (Corredoira et al 2008), Platanus occidentalis (Sun et al 2009), Jatropha curcas (Kumar et al 2010), Cassia angustifolia (Siddique et al 2010),Tabebuia donnell-smithii rose (GonzalezRodriguez et al 2010), Pterocarpus marsupium (Husain et al 2010), and Albizia lebbeck (Perveen et al 2011). …”
Section: Propagation By Adventitious Shoot Organogenesismentioning
confidence: 96%
“…Taylor et al, (1995) and Choudhuri et al, (2009) reported that PCR-based techniques such as RAPD and ISSR markers were successfully employed for the detection of variations at the genome level among regenerants. Since RAPD and ISSR techniques are simple and cost effective, it has been widely used by many researchers to assess genetic stability in micropropagated plants (Agnihotri et al, 2009; Chalageri and Babu 2012; Paul et al, 2010;Sun et al, 2009). Hence, in the present study we employed RAPD and ISSR analysis to check the genetic uniformity among the micropropagated plants and mother plant.…”
Section: Rapd and Issr Analysis Of Regenerated Plantsmentioning
confidence: 99%